KONSTRUKSI TINDAK PIDANA PEMBUNUHAN ANTARA DELIK PEMBUNUHAN BIASA (PASAL 338 KUHP) DENGAN DELIK PEMBUNUHAN BERENCANA - Simaremare, Yoseanna Anastasya; Mulyadi, Mahmud; Trisna, Wessy (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: This article analyzes the construction of criminal acts of murder, comparing ordinary murder (Article 338 of the Criminal Code) with premeditated murder (Article 340 of the Criminal Code), using the Ferdy Sambo case study (Decisions No.796/Pid.B/2022/PN Jkt.Sel, No.53/Pid/2023/PT DKI, and 813 K/Pid/ 2023). Criminal law imposes varied penalties; unpremeditated murder faces 15 years, while premeditated murder can result in death, life imprisonment, or 20 years. The Ferdy Sambo case, involving the murder of Brigadier YS on July 8, 2022, was charged under Article 340 of the Criminal Code. This research uses a normative descriptive analytical method. Ferdy Sambo was sentenced to death by the District Court and High Court, but the Supreme Court's cassation revised it to life imprisonment due to a dissenting opinion. Analysis shows the Judges inadequately considered subjective elements and lacked psychological expert opinion to assess the perpetrator's mental state for the "with prior planning" element of Article 340 of the Criminal Code. Additionally, no clear legal facts supported common intent (co-participation) between the defendant and RE as required by Article 55 Paragraph 1 Point 1 of the Criminal Code.Keyword: Premeditated Murder, Article 340 Criminal Code, Ferdy Sambo, Legal Analysis, Court Decision.Abstrak: Artikel ini menganalisis konstruksi tindak pidana pembunuhan, membandingkan delik pembunuhan biasa (Pasal 338 KUHP) dengan pembunuhan berencana (Pasal 340 KUHP), menggunakan studi kasus Ferdy Sambo (Putusan No.796/Pid.B/2022/PN Jkt.Sel, No.53/Pid/2023/PT DKI, dan 813 K/Pid/ 2023). Hukum pidana memiliki sanksi bervariasi; pembunuhan tanpa rencana diancam 15 tahun penjara, berencana dapat pidana mati, seumur hidup, atau 20 tahun. Kasus Ferdy Sambo, pembunuhan Brigadir YS pada 8 Juli 2022, didakwa dengan Pasal 340 KUHPidana. Penelitian ini menggunakan metode normatif deskriptif analitis. Ferdy Sambo divonis mati di PN Jakarta Selatan dan PT DKI, namun di kasasi MA diubah menjadi pidana penjara seumur hidup karena dissenting opinion hakim. Analisis menunjukkan Majelis Hakim kurang tepat mempertimbangkan unsur subjektif dan kurangnya pandangan ahli psikologi untuk mengukur kondisi mental pelaku dalam pembuktian unsur "dengan rencana terlebih dahulu" pada Pasal 340 KUHP. Juga, tidak ada fakta hukum jelas mengenai kesamaan kehendak (turut serta) antara terdakwa dan RE sebagai syarat Pasal 55 Ayat 1 Ke-1 KUHP. Kata kunci: Pembunuhan Berencana, Pasal 340 KUHP, Ferdy Sambo, Analisis Hukum, Putusan Pengadilan.